Thermodynamic interactions and characterisation of poly(isobornyl methacrylate) by inverse gas chromatography at various temperatures - Kaya, I; Özdemir, E (Elsevier Sci Ltd, 1999)
The inverse gas chromatography (IGC) method was applied to poly(isobornyl methacrylate) (PIBORNMA) as a method for polymer characterisation and for the study of thermodynamic interactions. Six groups of solvents with different chemical natures and polarities were used to obtain information about PIBORNMA-solvent interactions. The PIBORNMA-solvent interaction parameters and the free energy of mixing were determined at a series of temperatures. The glass transition temperature (T-g) of PIBORNMA was found to be about 105 degrees C by differential scanning calorimetry. The thermodynamic sorption functions for the sorption process of probes of differing chemical nature into PIBORNMA solution were obtained and discussed in terms of the probes' interactions with PIBORNMA. Furthermore, the contributions of -CH2, -C=O, -C=O-OR, aromatic, cyclic ether and -OH functional groups in the six series of solvents to the sorption process were also obtained. Acetates, THF and ketones were found to be good solvents for PIBORNMA, whereas alkanes, aromatics and methanol were found to be non-solvents. Also the solubility parameter for PIBORNMA at infinite dilution was found by plotting the graph of [(delta(1)(2)/RT) - chi(12)(infinity)/V-1] versus solubility parameters, delta(1), of some probes. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: thermodynamic parameters; solubility parameter; poly(isobornyl methacrylate)